Investment Real Estate Account Improvement Guidelines - A. Avlokulov; G. Mirzayeva (International Journal on Economics, Finance and Sustainable Development, 2022)
The topics of investment real estate accounting based on international standards are discussed in this article. On the basis of the findings of the research that was done, suggestions for enhancing the investment real estate account were made.